A Siamese Network based Writer Independent Offline Signature Verification (International Journal of Food and Nutritional Sciences, 2022)
Signatures are frequently used for both personal authorization and verification. Thesignatures on numerous papers, including legal agreements and bank checks, must beverified. Offline signature verification is a type of authentication that examines the physicalaction of signing while measuring the characteristics of an user's handwriting. In thepresent paper, an offline signature verification method was developed utilisingConvolutional Siamese Network of Deep Learning [4]. Convolutional Siamese networks,which are dual networks that shares parameters, can be developed to acquire a featuremap. Thus, Convolutional Siamese network is employed to verify the person's signature to ainput signature that is saved in the database. Research has been conducted with a datasetof signatures that includes 750 signatures from 30 different individuals. An Accuracy of91.6% was attained by the proposed solution.